Management tools in nursing care for children with pressure injury - Carla Braga Oliveira Rodrigues; Thiago Nascimento do Prado; Luciana de Cássia Nunes Nascimento; Mariana Rabello Laignier; Cândida Caniçali Primo; Maria Edla de Oliveira Bringuente (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objectives: to develop and validate management tools for the systematization of nursing care for children with pressure injuries. Methods: methodological study in which the focus group technique was used for validation of tools in three different groups of 17 nurses. Conducted in April and May 2018 at a large pediatric hospital. Results: two management tools were developed. The first was the Nursing care systematization instrument for children with pressure injury with three parts: a) risk factors; b) Psychobiological Basic Human Needs; c) signs of wound infection. The second was the Flowchart of pressure injury risk and prevention in pediatric patients with three categories: a) risk factors; b) Braden Q scale; c) nursing care. Final Considerations: the tools will support nurses in the care of children with pressure injuries by aiming at an individualized and systematized assessment based on a theoretical framework.